2012
DOI: 10.1093/humrep/des141
|View full text |Cite
|
Sign up to set email alerts
|

The duration of pre-ovulatory serum progesterone elevation before hCG administration affects the outcome of IVF/ICSI cycles

Abstract: Older patients (>42 years) are excluded from our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 49 publications
1
49
0
3
Order By: Relevance
“…Many studies have reported that a premature rise in progesterone is unfavorable on live birth outcome [17][18][19][20][21][22] following transfer of embryos in fresh IVF cycles. This phenomenon (premature luteinization) is unique to fresh cycles when the ovaries are driven by exogenously administered gonadotropins.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that a premature rise in progesterone is unfavorable on live birth outcome [17][18][19][20][21][22] following transfer of embryos in fresh IVF cycles. This phenomenon (premature luteinization) is unique to fresh cycles when the ovaries are driven by exogenously administered gonadotropins.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the duration of P elevation could have a stronger impact on cycle outcome than the absolute serum P concentration on the day of hCG. Th e clinical pregnancy rate is signifi cantly inversely correlated with the duration of premature serum P elevation above the cut-off value of 1.0 ng/mL, whatever the protocol used and the intensity of the ovarian response 19 . It seems that the use of a multivariable analysis is the proper way of assessing the adverse eff ect of preovulatory P elevation on live birth rates, when compared with the bivariate analysis that was used in most of the studies that failed to identify the detrimental eff ect in fresh IVF cycles 20 .…”
Section: Introductionmentioning
confidence: 97%
“…1 Ovülasyonun tetiklendiği gün yani insan koryonik gonadotropin [human chorionic gonadotropin (hCG)] günü, P yükselmesinin İVF sikluslarında gebelik sonuçları üzerine etkisi son 20 yıldır araştırılmaktadır. [2][3][4][5] Preovülatuar P yüksekliği endometriyal reseptiviteye zarar vererek devam eden gebelik oranlarını düşürmektedir. Ancak daha güncel çalışmalarda, GnRH antagonist sikluslarında P yüksekliğinin overyan yanıt düştükçe gebelik üzerine olumsuz etkisinin arttığı ortaya konmuştur.…”
unclassified